Molecular phylogenetics of Atlantic Shield Platynectes diving beetles (Coleoptera: Dytiscidae): a first glance at the evolution of the genus in the Amazon Basin. Issue 4 (3rd July 2016) - Toussaint, Emmanuel F.A.; Short, Andrew E.Z.
Summary: Neotropical diving beetles of the genus Platynectes are distributed across Central America, the Andes and different Precambrian shields in the Amazon Basin. Species from the northern Guiana Shield form a monophyletic clade, yet the phylogenetic relationships of the eastern Atlantic Shield species remain unknown. Here, we augmented an existing molecular dataset with a species from the Atlantic Shield that was not previously sampled. We reconstructed the phylogenetic relationships and estimated divergence times to understand the evolution of lineages dwelling in this region. The newly sampled specimens from the Atlantic Shield are recovered as sister taxa to Guiana Shield species. The dating analyses suggest a split between these two lineages in the late Oligocene to mid-Miocene, contemporary with the Miocenic geological remodeling of the Amazon Basin. Additional sampling in the Atlantic and Central Brazilian Shields will be determinant to test the monophyly of Platynectes species distributed in these ancient shields, and to fully understand the biogeographical history of diving beetles in the Amazon Basin.